Synchronous Presentation of Rare Brain Tumors in Von Hippel–Lindau Syndrome - Mariachiara Lodi; Antonio Marrazzo; Antonella Cacchione; Marina Macchiaiolo; Antonino Romanzo; Luciano Mastronardi; Francesca Diomedi-Camassei; Alessia Carboni; Andrea Carai; Carlo Gandolfo; Lidia Monti; Angela Mastronuzzi; et al. (Diagnostics, 2021)
Von Hippel–Lindau (VHL) disease is a heritable cancer syndrome in which benign and malignant tumors and/or cysts develop throughout the central nervous system (CNS) and visceral organs. The disease results from mutations in the VHL tumor suppressor gene located on chromosome 3 (3p25-26). A majority of individuals (60–80%) with VHL disease will develop CNS hemangioblastomas (HMG). Endolymphatic sac tumor (ELST) is an uncommon, locally aggressive tumor located in the medial and posterior petrosal bone region. Its diagnosis is based on clinical, radiological, and pathological correlation, and it can occur in the setting of VHL in up to 10–15% of individuals. We describe a 17-year-old male who presented with a chief complaint of hearing loss. Brain and spine Magnetic Resonance Imaging documented the presence of an expansive lesion in the left cerebellar hemisphere, compatible with HMG in association with a second cerebellopontine lesion compatible with ELST. The peculiarity of the reported case is due to the simultaneous presence of two typical characteristics of VHL, which led to performing comprehensive genetic testing, thus allowing for the diagnosis of VHL. Furthermore, ELST is rare before the fourth decade of life. Early detection of these tumors plays a key role in the optimal management of this condition.